Tuam Cathedral, fourteenth-century choir, interior south wall, sedilia, base - O'Donovan, Danielle (My University, 2008)
Sedilia base, moulding from top down comprises roll, hollow, roll-and fillet, hollow, fillet, roll. The middle roll-and-fillet forms a water-holding element.
Sedilia
Keywords: water-holding base; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Late Medieval; roll-and-fillet moldings; roll moldings